The potentiometric response of polypyrrole electrosynthesised in alkaline media - Saidman, Silvana Beatriz (2005)
The study has been focused on the potentiometric response of polypyrrole films electrosynthesised in alkaline solutions onto vitreous carbon electrodes. The influence of different conditions for electropolymerisation and soaking on the potentiometric sensitivity of the film is analysed. A simple model allows to interpreting the ion sensitivity observed. The participation of OH - in the ion-exchange process is demonstrated, in agreement with previous results.